Transformasi Pola Komunikasi Dakwah FPI melalui Perubahan Strategi Penyampaian Pesan Keagamaan - Rismayati, Eva; Junaedi, Jujun (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2014)
The purpose of this study is to determine the input of change, target element of change, and output the organizational change of Front Persaudaraan Islam. The method used is a case study. The results of this studi are that there are 4 inputs or reason for the change, first, because of the dissolution by the government; second, the strategy of introducing a new FPI; third, changing the paradigm of society; and fourth, maintain the continuity of da’wah. The target element of change are the name, logo, vision and mission, management structure, subsidiary organizations, motto, three battlefields, messages, media and methods. And the output or impact of this change are improving and strengthening the existence of the organizations, changing the paradigm of society, increasing the fighting spirit of members and improving the administrative structure.